WAWASAN AL-QUR’AN TENTANG INTEGRITAS, STUDI AL-QURAN TEMATIK DENGAN PENDEKATAN GROUNDED THEORY - Muhammad Irsyad Mu’afa; Muhammad Alif (CV. Adiba Aisha Amira, 2025)
This study aims to explore the concept of integrity from the perspective of the Qur'an using the thematic study method (maudhu'i) combined with a grounded theory approach. The background of this study departs from the problem of the integrity crisis that plagues contemporary society, such as rampant corruption, information manipulation, and a weak sense of responsibility. The Qur'an as the holy book of Muslims presents fundamental values that are relevant to address these challenges. By using the method of collecting and analyzing Qur'anic verses related to integrity (amanah, shidq, istiqamah, and responsibility), this study found that Qur'anic integrity encompasses spiritual and social dimensions. The grounded theory approach allows for the formation of a new theoretical construction of integrity based on the Qur'an, which not only provides honesty in social interactions but also continues to spiritual commitment to Allah SWT. This study concludes that integrity in the Qur'an is a transcendental value that is the basis for the formation of a civilized person and society.